2020
DOI: 10.3390/jcm9103305
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Minimal Clinically Important Differences for Knee Range of Motion after Stroke

Abstract: The importance of knee sagittal kinematic parameters, as a predictor of walking performance in post-stroke gait has been emphasised by numerous researchers. However, no studies so far were designed to determine the minimal clinically important differences (MCID), i.e., the smallest difference in the relevant score for the kinematic gait parameters, which are perceived as beneficial for patients with stroke. Studies focusing on clinically important difference are useful because they can identify the clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
0
27
1
1
Order By: Relevance
“…5.7° [ 65 ]) and the minimal clinically important difference for knee sagittal range of motion in stroke survivors (i.e. 8.48° [ 66 ]). As improved post-stroke knee kinematics may promote safe foot clearance [ 12 ], it might be interesting for future studies to investigate intervention effects on both propulsion and knee kinematics in a larger group of stroke survivors with reduced knee flexion during swing at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…5.7° [ 65 ]) and the minimal clinically important difference for knee sagittal range of motion in stroke survivors (i.e. 8.48° [ 66 ]). As improved post-stroke knee kinematics may promote safe foot clearance [ 12 ], it might be interesting for future studies to investigate intervention effects on both propulsion and knee kinematics in a larger group of stroke survivors with reduced knee flexion during swing at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the results reported by both Chai et al and Deng et al 7,8 Since the MCID of the ROM following KA has not been reported in previous literature, it may be premature to draw conclusions regarding whether the addition of corticosteroids to LIA enhances functional recovery of the knee. Recently, researchers have attempted to estimate the MCID for the ROM post‐stroke; their MCID estimates of the knee sagittal ROM were 8.48°and 6.81° for the affected and unaffected knees, respectively 43 . Because of the differences in baseline measures between the knee after stroke and the knee after arthroplasty, the statistically significant change observed on postoperative day 1 (MD = 9.14) may not be one that matters to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…MCID is defined as "the smallest difference in score in the domain of interest which patients perceive as beneficial and which would mandate (...) a change in the patient's management" (16). So far, MCID has been calculated for only one of the above major 3DGA kinematic predictors of walking performance post-stroke, i.e., for knee (17). In addition to that, some related studies have aimed to determine the minimal detectable change (MDC) in individuals post-stroke (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…This study is the second part of a broader research project. The first part aimed to estimate the MCID for knee range of motion (ROM) in the sagittal plane for the affected and unaffected side at a chronic stage post-stroke ( 17 ). Taking into consideration the aforementioned facts, we have decided to continue the related research, this time focusing on the kinematic parameter of hip sagittal ROM, in line with the evidence suggesting the high reliability of 3DGA ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation